The philosophical idea of a new Christian civilization in Russian Religious Philosophy - Rarot, Halina (Studia z Historii Filozofii, 2023)
The article argues, using the thought of Fyodor Dostoevsky and Nikolai Berdyaev as an example, that the search for the genesis of the current political ideology, guiding the armed conflict launched by Russia in Ukraine, in the thought represented by Russian religious philosophers of the second half of the 19th and early 20th centuries, i.e., the founders of a strictly national philosophy, is quite superficial and essentially unfounded. For the idea of a new Christian civilization with a new state order and a new role for the Orthodox Church, which they formulated, was an idea of such a Christian reality, the fulfilment of which, in their view, could only occur at a very distant time, actually at the end of human history, and required an earlier spiritual and moral revolution.